Effect of Organizational Change on Employee Job Involvement: Mediating Role of Communication, Emotions and Psychological Contract - Khalid, Arfan (Information Management and Business Review, 2011)
The purpose of the current paper is to provide a conceptual framework for studying the impact of organizational change on employee job involvement while communication, emotions and psychological contract plays mediating role in this relationship. The current study conceptualize that organizational change followed by effective communication generate the positive emotions which ultimately increase the employee job involvement where as organizational change with ineffective communication causes negative emotions which results in low employee job involvement. The study also founds that organizational change may break the psychological contract between employee and employer which reduces the employee job involvement.